RANCANG BANGUN PENENTUAN MAHASISWA BERPRESTASI BERBASIS WEB DENGAN METODE TOPSIS PADA FAKULTAS ILMU KOMPUTER UPN VETERAN JAKARTA - Hendi Triatmoko (2021)
In appreciating students who have been active in studying until graduation, the Jakarta Veteran National Development University gives a mahardika predicate for students on its campus who have the best grades and achievements to appreciate the hard work of students during their studies. To determine the selected student, who gets a mahardika degree needs to be supported by accurate data from accurate data from student data and compensation in order to get accurate results. Computing is necessary in managing the data of students who excel, so a computation media in the form of a website-based application is created, with the aim of providing updated digital information to students. Through the website, it is used as a forum for delivering information to expose the list of outstanding students and so on, so that data that students need to know can be conveyed in a transparent manner. The data needed include student achievement data and weight data of predetermined criteria. The design of this website-based student determination system was built using the TOPSIS method. Other software requirements are Xampp used as a local server during system development, phpMyAdmin as a database operator, MySQL database, and software vs code as a place for website program code generation. The final result of designing and building this website as a decision support system tool for the selection of students with mahardika achievement at the Faculty of Computer Science UPN Veteran Jakarta.